Asumsi Rasionalitas dalam Prilaku Konsumsi Perspektif Ekonomi Mikro Islam - Siswadi Siswadi; Wilda ‘Ainun Najihah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The term Rationality will look confusing if it has many meanings or meanings, and sometimes rationality does not match what is expected. Rationality is a mindset in acting in accordance with human reason and logic. Specifically, rationality can also be said as a tendency to fulfill long-term plans, taking into account all the risks and benefits of the actions taken. Rationality is a consequence on the basis of economic and religious factors, where the main factor becomes the basic basis in the discussion of capitalist development. A person's choice can be said to be rational if this choice as a whole can be explained by the terms of the preferred consistent relationship with the definition of the appearance of the preferred choice. the decisions taken by these individuals should lead to the quantification of the final decision in monetary units. Quantification will lead to calculations and tend to maximize the goals of each activity.